Tychobythinus inopinatus, a new troglobitic species from Sicily (Coleoptera, Staphylinidae, Pselaphinae) - Sabella, Giorgio; Costanzo, Salvatore; Nicolosi, Giuseppe (Zootaxa, 2020)
A new troglobitic species of the subfamily Pselaphinae (Coleoptera: Staphylinidae), Tychobythinus inopinatus sp. nov., is described from Monello Cave (Syracuse, Syracuse Province, Sicily). Major diagnostic features are illustrated based on both male and female specimens. The new species shows some adaptations to cave life, i.e., pale brown colour; setation consisting of long and flattened setae and suberect shorter setae; absence of wings; and anophthalmy and elongate legs and antennae. It can be easily separated from the related taxa by the different shapes of the head, palpi, gular carina of the male, and aedeagus. Tychobythinus inopinatus sp. nov. is known only from Monello Cave, a limestone cave in the south-eastern Sicily.